Differential Gene Expression Analysis of Human Atrial Fibroblasts Reveals Dysregulation of RNA Metabolism and Translational Machinery in Atrial Fibrillation - Padidam Lakshmi Sravya (International Journal of Bioinformatics and Computational Biology, 2026)
Atrial fibrillation (AF) is a complex cardiac arrhythmia characterized by extensive structural remodeling and the activation of atrial fibroblasts, which drive the progression of fibrosis. To identify the underlying transcriptomic alterations, we analyzed six human atrial fibroblast RNA-Seq datasets (three control and three AF) retrieved from the Sequence Read Archive. After performing rigorous quality control and adapter trimming, we aligned the reads to the GRCh38 human reference genome using a splice-aware mapping approach. Differential expression analysis was conducted within a negative binomial framework, ultimately identifying 78 genes that were significantly dysregulated in AF samples (adjusted p-value 1). Principal component analysis (PCA) demonstrated a clear transcriptional divergence between the conditions, highlighting a distinct molecular signature associated with the disease state. Functional enrichment analysis revealed that these dysregulated genes are heavily involved in cytoplasmic translation, RNA splicing, and ribosome biogenesis. These findings suggest that AF-associated remodeling in fibroblasts is mediated by specific perturbations in RNA metabolism and translational control. Consequently, this study provides a new framework for exploring post-transcriptional regulatory mechanisms as potential therapeutic targets for managing AF.
Keywords: Atrial fibrillation; RNA sequencing; atrial fibroblasts; cardiac fibrosis; differential gene expression; transcriptomic analysis